Christian anthropology and personhood in the Catholic undergraduate psychology curriculum - Houde, Keith A. (Journal of psychology and christianity, 2016)
The well-known scripture passage, "What is man that thou art mindful of him, and the son of man that thou dost care for him?" (Psalm 8:4, RSV), generates many important [...]This study surveyed the undergraduate psychology curricula and select aspects of the general education curricula of Catholic colleges and universities recommended by the Cardinal Newman Society in 2014. A review of academic catalogues (2014-2015) revealed relatively cohesive psychology course offerings across the 21 programs surveyed, along with variability in frequency of required courses across programs. Curricular content of these programs compared favorably with current (2013) APA Guidelines for the Undergraduate Psychology Major. Intentional consideration of Christian anthropology and views of personhood was found less frequently than expected within the psychology curricula of these programs; however, general education offerings often provided opportunity to explore and better understand a Christian perspective on the nature of persons. Preliminary recommendations are presented regarding a curriculum that is true to the person.